Design optimization for energy consumption in residential buildings through building information modeling - Hassanabadi, Mahmoud Shakouri (2012)
Green building has now become a flagship of sustainable development in Malaysia that takes the responsibility for balancing long-term economic, environmental and social health. High total load green house gas emissions and inefficient energy consumption are the issues that the building sector in Malaysia is struggling with. To cope with these issues, Malaysian construction industry has been urged to use more innovative construction techniques like industrialized Building System and Building Information Modeling. This paper aims at evaluating the efficiency of different approaches taken to minimize the cooling load in the building. For this purpose site orientation, type of fenestration, building materials and building layout redesign are studied. The case study in this paper is a double storey bungalow located in Johor Bahru. It was modeled in Revit Architecture and exported to Autodesk Ecotect Analysis for energy simulation. Results show that by modifying building materials and utilizing energy efficient windows and wall component, the cooling load can be reduced up to 33%. It was also concluded that by proper utilizing and scheduling the HVAC operation time, this reduction can soar up to 72%